Sharing the land of Canaan : human rights and the Israeli-Palestinian struggle - Qumsiyeh, Mazin B. (Pluto Press ; University of Michigan Press, 2004)
Examines human rights issues in the Occupied Territories and lays out plans for a lasting peace.